Toward an Attentive Robotic Architecture: Learning-Based Mutual Gaze Estimation in Human–Robot Interaction - Lombardi, Maria; Maiettini, Elisa; De Tommaso, Davide; Wykowska, Agnieszka; Natale, Lorenzo (Frontiers in Robotics and AI, 2022)
Social robotics is an emerging field that is expected to grow rapidly in the near future. In fact, it is increasingly more frequent to have robots that operate in close proximity with humans or even collaborate with them in joint tasks. In this context, it is still an open problem the investigation of how to endow a humanoid robot with social behavioural skills typical of human-human interactions. Among the countless social cues needed to establish a natural social attunement, the paper reports our research towards the implementation of a mechanism for estimating gaze direction, focusing in particular on mutual gaze as fundamental social cue in face-to-face interactions. We propose a learning-based framework to automatically detect eye-contact events in online interactions with human partners. The proposed solution achieves high performance both in silico and in experimental scenarios. Our work is expected to be the first step towards an attentive cognitive architecture able to endorse scenarios in which the robots are perceived as social partners.